Coronary CT angiography: How should physicians use it wisely and when do physicians request it appropriately? - Sun, Zhonghua; Abdul Azizb, Yang; Ng, Kwan-hoong (Elsevier Ireland Ltd, 2012)
Coronary CT angiography has been increasingly used in the diagnosis of coronary artery disease due to rapid technological developments, which are reflected in the improved spatial and temporal resolution of the images. High diagnostic accuracy has been achieved with 64- and more slice CT scanners and in selected patients, coronary CT angiography is regarded as a reliable alternative to invasive coronary angiography. Although the tremendous contributions of coronary CT angiography to cardiac imaging are acknowledged, appropriate use of cardiac CT as the first line technique by physicians has not been well established. Optimal selection of cardiac CT is essential to ensure acquisition of valuable diagnostic information and avoid unnecessary invasive procedures. This is of paramount importance since cardiac CT not only involves patient risk assessment, prediction of major cardiac events, but also impacts physician decision-making on patient management. Applications of CT in cardiac imaging include coronary artery calcium scoring for predicting the patient risk of developing major cardiac events, followed by coronary CT angiography which is commonly used to determine the diagnostic and prognostic accuracy in the coronary artery disease. This review presents an overview of the applications of CT in cardiac imaging in terms of coronary calcium scoring and coronary CT angiography. Judicious use of both cardiac CT tools will be discussed with regard to their value in different patient risk groups with the aim of identifying the appropriate criteria for choosing a cardiac CT modality. An effective diagnostic pathway is finally recommended to physicians for appropriate selection of cardiac CT in clinical practice.